Industry Revolution 4.0: Strengthening the Creative Economy Sectors through BEKRAF Implementation Programs - I WAYAN ADITYA HARIKESA (TRANSBORDERS: International Relations Journal, 2020)
President Joko Widodo or Jokowi has made a great leap in enhancing Indonesia’s Small Medium Enterprises (SME)s and the country’s overall creative industries by establishing a new non ministerial institution called Badan Ekonomi Kreatif (BEKRAF) or the Creative Economy Agency. The BEKRAF, established under the Presidential Regulation Number 6 of 2015 issued on January 20, 2015, is responsible for accelerating the development of creative economy in Indonesia. Small Medium Enterprises (SMEs) have been playing crucial roles for generating economic progresses as well as social inclusion in Indonesia. Among the most important and worthy of priority is the country’s creative economy. The existence of BEKRAF will enhance close cooperation between the government, SMEs players and related economic stakeholders. This paper aims to assess the concept of “Creative Industries,” as a boundary concept that allows for increased co-operation between players and the generally opposing knowledge concepts—as reflected in their respective knowledge and cultural politics. Indonesia has great potential in terms of economic growth. In 2015, Indonesia’s Gross Domestic Product (GDP) rocketed to 4.79 percent, far above the previous expectation of only 2.4 percent. This encouraging climate is indeed the right moment for the government to strengthen the country’s economic foundation particularly in the real economic sector. Hence, BEKRAF has a vision to build Indonesia as one of the world’s great economic powers in the field of creative economy by 2030. This issue will be discussed comprehensively in the final part of the paper. Key words: BEKRAF, Creative Industries, Creative Economy